2015
DOI: 10.1111/cea.12668
|View full text |Cite
|
Sign up to set email alerts
|

Comparable actions of omalizumab on mast cells and basophils

Abstract: Our data prove the existence of common mechanisms of action of OmAb in mast cells and basophils that would explain its effectiveness and rapid effect in chronic urticaria and provide a basis for its use in other diseases mediated by these cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 43 publications
5
47
0
1
Order By: Relevance
“…This observation was confirmed by Serrano-Candelas et al [25] on mast cells. They also proved that this phenomenon is associated with IgE-dependent decreased signalling from FceRI, connected with inhibition of proximal phosphorylation in the Syk-LAT-PLCg axis, as well as inhibition of degranulation and synthesis of leukotrienes.…”
Section: Pharmacodynamic Properties Of Omalizumabsupporting
confidence: 73%
“…This observation was confirmed by Serrano-Candelas et al [25] on mast cells. They also proved that this phenomenon is associated with IgE-dependent decreased signalling from FceRI, connected with inhibition of proximal phosphorylation in the Syk-LAT-PLCg axis, as well as inhibition of degranulation and synthesis of leukotrienes.…”
Section: Pharmacodynamic Properties Of Omalizumabsupporting
confidence: 73%
“…Interestingly, in recent years, the drug's action has been shown to go further, dissociating bound IgE from the IgE-Fc ε RI complex (mechanism (2) in Figure 3) [46, 47]. Thus, at a physiological concentration range, OmAb may accelerate the dissociation of the preformed IgE-Fc ε RI complex on the surfaces of mast cells and basophils in addition to its ability to neutralize the free IgE, leading to an impairment of the IgE-inflammatory signaling cascade [47]. Moreover, the density of Fc ε RI expression on basophils, mast cells, and dendritic cells falls notably in patients receiving anti-IgE treatment within the first week of OmAb application [8].…”
Section: Anti-ige-based Treatmentsmentioning
confidence: 99%
“…These findings suggested another mechanism of action for OmAb, apart from its ability to sequester free IgE. Lowering free IgE levels may downregulate the levels of IgE receptor expression density on the surface of mast cells in the long term, but this would not appear to be responsible for the rapid improvement reported in the clinical symptoms; a more likely reason is OmAb's ability to dissociate prebound IgE from Fc Ɛ RI [46, 47]. Nevertheless, it is still unclear how OmAb works in CSU: in addition, the fact that OmAb is not effective in all patients suggests the involvement of mechanisms/pathways in CSU other than the IgE cascade.…”
Section: Anti-ige-based Treatmentsmentioning
confidence: 99%
“…Food allergens likewise induce a shift toward Th2 immunity and sensitize the MCs by binding to their FcεRI receptors[52]. Monomeric IgE can enhance MC activity and mediator release[53]. Sensitization of MCs with monoclonal IgE stimulates up-regulation of genes encoding the inflammatory cytokines, chemokines, cytokine and chemokine receptors, adhesion molecules, anti-apoptosis proteins and cytoskeletal elements[52].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that a human monoclonal IgE can stimulate MCs to produce histamine-releasing factor[54]. Omalizumab, itself, has been shown to sequester monomeric IgE, thereby reducing its priming effect on MCs[53]. …”
Section: Introductionmentioning
confidence: 99%